Geospatial Mapping Of Selected Heavy Metals Based On Land Use Within Kinta River Catchment - Effendi, Nurul Farah Syafiqah Mohd (Universiti Sains Malaysia, 2022)
The Kinta River catchment is a significant river network that flows through the city of Ipoh and functions to supply water to the residents for consumption purposes. This research study has been conducted to assess the status of the water quality based on the selected parameters as well as the concentration of heavy metals in order to understand the present scenario of water quality of the downstream of Kinta River. In this study, five in-situ parameters had been analyzed including total dissolved solids, dissolved oxygen, pH, salinity, and temperature followed by two laboratory parameters involving total suspended solids and turbidity. A total of 21 types of heavy metals are being analyzed by using ICP-OES. However, only 9 significant heavy metals that are being discussed in this study such as arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), magnesium (Mg), manganese (Mn), lead (Pb) and zinc (Zn). TMDL and ArcGIS are being used to show the distribution of heavy metals throughout Kinta River catchment and to calculate the amount of heavy metals released into the river. Based on this study for in-situ parameters, the temperature, pH, dissolved oxygen, salinity, and total dissolved solids are ranging from 24.4 to 30.4℃, 5.88 to 6.37, 4.39 to 8.98 mg/L, 0.01 to 0.09 ppt and 17.55 to 126.1 mg/L respectively. As for laboratory analysis, total suspended solids and turbidity recorded a value ranging from 11.7 to 63.7 mg/L and 14.43 to 97.67 NTU for each parameter. Next, for heavy metals, there are no presence of copper (Cu), lead (Pb) and zinc (Zn) detected at these 22 sampling points throughout Kinta River catchment. Chromium and cadmium had only been detected at the upstream of Kinta River. Arsenic, iron, magnesium, and manganese values are ranging from 0.01972 to 0.136286 mg/L, 0.143418 to 1.13776 mg/L, 1.29807 to 4.58733 mg/L and 0.01452 to 0.164668 mg/L respectively. Next, ArcGIS is used to show the dispersion of these parameters in a map throughout Kinta River catchment along with TMDL calculations.